2016
DOI: 10.1128/microbiolspec.tbtb2-0017-2016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection Models of Tuberculosis in Domestic Livestock

Abstract: In this article we present experimental Mycobacterium bovis infection models in domestic livestock species and how these models were applied to vaccine development, biomarker discovery, and the definition of specific antigens for the differential diagnosis of infected and vaccinated animals. In particular, we highlight synergies between human and bovine tuberculosis (TB) research approaches and data and propose that the application of bovine TB models could make a valuable contribution to human TB vaccine rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…This in turn can generate confidence in the interpretation of results from experimental vaccine—challenge studies. In many domestic species, e.g., cattle, goats, and deer, the presentation of tuberculosis is similar to that observed in the greater majority of infected humans in that it is a chronic, slowly progressive disease with pathology predominantly confined to the lower respiratory tract, with associated cellular immune responses ( 73 , 74 ). However, the occurrence and prevalence of latency in these species has not been clearly established and is difficult to identify in either natural-infected or experimentally infected animals.…”
Section: Experimental Infection Models For Domestic Species and Wild mentioning
confidence: 89%
“…This in turn can generate confidence in the interpretation of results from experimental vaccine—challenge studies. In many domestic species, e.g., cattle, goats, and deer, the presentation of tuberculosis is similar to that observed in the greater majority of infected humans in that it is a chronic, slowly progressive disease with pathology predominantly confined to the lower respiratory tract, with associated cellular immune responses ( 73 , 74 ). However, the occurrence and prevalence of latency in these species has not been clearly established and is difficult to identify in either natural-infected or experimentally infected animals.…”
Section: Experimental Infection Models For Domestic Species and Wild mentioning
confidence: 89%
“…Most domestic mammalian species are susceptible to experimental infection. The most developed experimental models of infection of livestock are: cattle (Dean et al., ; Buddle et al., ), camelids (Stevens et al., ), pigs (Bolin et al., ), goats (de Val Pérez et al., ; Gonzalez‐Juarrero et al., ), and deer (Palmer et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Previous studies have shown that the pathogenesis of bTB disease is similar to TB disease in humans and many of the features of M. tuberculosis infection are also characteristic of M. bovis infection in cattle (Buddle et al, 2016; Waters et al, 2014; Williams and Orme, 2016). Transmission is via inhalation of contaminated aerosol droplets and the primary site of infection is the lungs where the bacilli are phagocytosed by alveolar macrophages, which normally can contain or destroy intracellular bacilli (Kaufmann and Dorhoi, 2016; Weiss and Schaible, 2015).…”
Section: Introductionmentioning
confidence: 96%